Molecular docking analysis of guaiacin and chalcone from nutmeg (Myristica fragrans) as novel HSP90A inhibitors for skin cancer treatment - Arrafi, Muhammad Zhafran; Cahyani, Ayu Sukma; Sitohang, Nada Nikita; Ulya, Salsa Nabila Ahlika; Anggraeni, Inggrid; Amalia, Miranti; Putri, Gladys Ellnora; Rajwa, Raihan M Dhiya; Auli, Winni Nur; Saputro, Anjar Hermadi (Pharmacy Reports, 2023)
Skin cancer represents one of the most prevalent malignancies globally, with Indonesia reporting the third highest incidence among cancer types. Despite advances in treatment, there remains a critical need for novel therapeutic agents. Heat Shock Protein 90 Alpha (HSP90A) has emerged as a promising target for cancer therapy due to its critical role in stabilizing oncogenic proteins. This study aimed to evaluate the potential of guaiacin and chalcone from nutmeg (Myristica fragrans) as HSP90A inhibitors for skin cancer treatment through computational analysis. Molecular docking was performed using AutoDock Tools with the HSP90A crystal structure (PDB ID: 2VCJ). The compounds were assessed for binding affinity, molecular interactions, and drug-likeness properties according to Lipinski's Rule of Five. Redocking validation yielded an RMSD of 1.24 Å, confirming protocol reliability. Guaiacin demonstrated promising binding affinity (-7.40 kcal/mol) with key hydrogen bonds to Asp93 and Lys58, while chalcone showed moderate affinity (-5.99 kcal/mol) with a single hydrogen bond to Thr184. Both compounds exhibited favorable drug-like properties with high predicted gastrointestinal absorption. Guaiacin emerges as a promising natural HSP90A inhibitor candidate with binding energy exceeding the stability threshold (-7.00 kcal/mol) and interactions with critical residues in the ATP-binding pocket, providing a foundation for further development of nutmeg-derived compounds as potential anticancer agents.